How does it work? The evidence for radio's effectiveness - Barber, Mark (Henry Stewart Talks, 2008)
All advertising activity is assessed on the results it produces, Radio particularly needs evidence of its effectiveness as it is consumed in private and leaves no trace once it has elapsed, you literally can't "see it working", Review of significant studies into radio's effectiveness as a medium in terms of driving awareness and sales, and delivering business results for brands, Review of the effect of radio in combination with other media press (TV, newspapers and internet), Best research carried out in UK and the USA, Most insightful case studies
Archived at 2022/03/17